Over the head and lateral position technique for cardiopulmonary resuscitation: which one is better? - Feorentina, Ivo; Putra, Kuswantoro Rusca; Suryanto, Suryanto (Universitas Muhammadiyah Purwokerto, 2020)
Background: A high rate of cardiac arrest requires high-quality CPR. A valuable CPR rescuer has lower success than two or more rescuers, especially with the use of BVM. There is a complexity encountered with lateral CPR position as a commonly used position, which is the difficulty of position movement from compression to ventilation. On the other hand, Over the Head CPR position is used as an alternative position, which is considered more effective than a lateral position. It is also considered to be able to overcome the obstacles found in CPR with a single rescuer using BVM ventilation in the lateral position so that study is required to compare the quality of CPR between the two CPR positions.Technique: The quality of CPR between Over the Head position CPR and Lateral position CPR is compared. The technique testing was carried out on 24 students using a mannequin. CPR quality components include compression ratios: ventilation, speed, depth, hand placement, chest recoil, and the amount of time of chest compression interruption were observed strictly. The overall CPR quality score, particularly in terms of compression speed and the minimum interruption time of chest compression on Over the Head position, is better than lateral position CPR.Conclusion: Over the Head position, CPR significantly produces a better quality of CPR than Lateral position CPR.